2020
DOI: 10.1002/advs.202001860
|View full text |Cite
|
Sign up to set email alerts
|

A Pumpless Microfluidic Neonatal Lung Assist Device for Support of Preterm Neonates in Respiratory Distress

Abstract: Premature neonates suffer from respiratory morbidity as their lungs are immature, and current supportive treatment such as mechanical ventilation or extracorporeal membrane oxygenation causes iatrogenic injuries. A non‐invasive and biomimetic concept known as the “artificial placenta” (AP) would be beneficial to overcome complications associated with the current respiratory support of preterm infants. Here, a pumpless oxygenator connected to the systemic circulation supports the lung function to relieve respir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…However, significant barriers to expanded use of ECMO technology remain, particularly associated with the complexity of the blood circuit and anticoagulant administration. In response to these challenges, microfluidic oxygenators have emerged as a compelling means to address many of the safety and efficacy-related concerns with current ECMO procedures, driven in particular by opportunities to better mimic blood flow patterns in the natural lung and thereby avoid high rates of thrombus formation and heavy reliance on anticoagulant administration [ 17 , 23 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, significant barriers to expanded use of ECMO technology remain, particularly associated with the complexity of the blood circuit and anticoagulant administration. In response to these challenges, microfluidic oxygenators have emerged as a compelling means to address many of the safety and efficacy-related concerns with current ECMO procedures, driven in particular by opportunities to better mimic blood flow patterns in the natural lung and thereby avoid high rates of thrombus formation and heavy reliance on anticoagulant administration [ 17 , 23 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scaling of the microfluidic oxygenator technology is often considered in terms of two directions. A given blood-membrane-gas sandwich structure can be scaled vertically by stacking these sandwich structures and interconnecting them with manifolds to integrate the blood and oxygen flows, as has been described previously [ 23 , 25 , 31 ]. A principal challenge this approach faces is the need for a very large number of layers in the stack [ 33 ], resulting in complexity in the assembly process as well as large increases in the blood prime volume in manifold regions not associated with blood–gas transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Very recently, Dabaghi et al operated a microfluidic, artificial placenta-type neonatal lung assist device (LAD) on a newborn piglet with respiratory distress. [1] Results from the piglet experiments revealed the effectiveness of this LAD in gas exchange without complications. The authors indicated that the LAD has a potential application as a biomimetic artificial placenta to support the respiratory needs of preterm neonates.
…”
mentioning
confidence: 92%